The decentralization of race: tracing the dilution of racial equity in educational policy. Issue 4 (20th April 2020) - Felix, Eric R.; Trinidad, Adrián
Abstract: This article examines California's Student Equity Policy crafted by policymakers to "avoid an underclass of ethnic minorities" in higher education. We combine tenets from critical race theory, interest convergence, and color-evasiveness to qualitatively interrogate 17 policy documents including chaptered bills, legislative mandates, and implementation guidelines related to the reform effort. We highlight how revisions to the reform deliberately inoculated a race-conscious policy into an effort targeting all students. Over the policy's 25-year history, we found that policymakers continuously diluted the role of race and opportunities to address racial disparities in legislative mandates. Implications for this research emphasize the significant role of policymakers in crafting legislation that explicitly draws attention to inequities faced by racially minoritized students in higher education. It considers practitioners' ability to implement these policies in ways that can improve racial equity. We conclude by sharing recommendations for scholars seeking critical approaches to understand how racially minoritized students benefit, or not, from equity initiatives crafted by policymakers.